Low Prevalence of Active Tuberculosis among High-Risk Pregnant and Postpartum Women in Sweden: A Retrospective Epidemiological Cohort Study Using and Evaluating TST as Screening Method - Maria Bullarbo; Martina Barnisin; Nina Vukas Radulovic; Åsa Mellgren (Hindawi Limited, 2018)
Objective. Studies on the prevalence of active tuberculosis (TB) and latent tuberculosis infection (LTBI) among high-risk pregnant and postpartum women are few and prevalence is not well known. The methods used for diagnosing and treating TB and LTBI also differ both within and between countries. The aim of the study was to investigate the prevalence of TB and LTBI among high-risk pregnant and postpartum women in a Western Region of Sweden using tuberculin skin test (TST) as screening method. Secondary aims were to evaluate the effectiveness of the screening method and possible negative labour and neonatal outcomes among TST-positive women. Methods. Pregnant women attending an antenatal care unit (ACU) allocated for TST screening were investigated and followed up for two years postpartum. Results. Only one woman out of 902 screened women in the study group was diagnosed with active TB because of TB symptoms and not because of positive TST. 36% of the skin-tested women fulfilled criteria for LTBI. No difference in perinatal outcome was found between women with and without positive TST. Conclusions. Our findings suggest that TST screening of high-risk women may not be an effective strategy, since the prevalence of active TB is low. Investigating pregnant and postpartum women with TB symptoms instead of TST for screening could be an option in low TB prevalence areas. The criteria for diagnosing and treating LTBI should be clearly stated.